CADISS Revealed Low Recurrent Stroke Rate in Patients With Cervical Artery Dissection. Issue 2 (11th March 2015) - Zarifyan, Alla
The CADISS trial investigated the efficacy of antiplatelet vs anticoagulant treatment in preventing stroke in patients with acute cervical artery dissection. The feasibility phase revealed that the sample size for a definitive study would have to be approximately 10 000 patients. However, it showed that recurrent stroke rate was much lower than previously reported.